Effects of food price shocks on child malnutrition: The Mozambican experience 2008/09 - Channing Arndt; M. Azhar Hussain; Lars Peter Østerdal (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
A propitiously timed household survey carried out in Mozambique over the period 2008-09 permits us to evaluate the short-to-medium run relationship between sudden shocks to food prices and child nutrition status. We link local price inflation with child malnutrition status. We find that the prevalence of underweight amongst children rises in response to a higher inflation rate for basic food products. Stunting and wasting malnutrition measures are mostly insensitive to the inflation rate. The very high food inflation during 2008/09 was responsible for an extra 39,000 moderately underweight and 24,000 severely underweight children.
Keywords: C51; D12; I32; O12; 330; food prices; inflation; child malnutrition; Mozambique; short to medium-run relationship; Lebensmittelpreis; Inflation; Mangelernährung; Kinder; Mosambik